Introduction to Surgery for Students - Fisher, Rebecca A.; Ahmed, Kamran; Dasgupta, Prokar (Springer International Publishing : Imprint: Springer, 2017)
This book provides a one-stop guide to the basics of surgery for surgical rotations, as well as information for aspiring surgeons on how to explore a surgical career and build your CV for surgical applications. It is the perfect go-to companion for any student shadowing in theatres, and a thorough guide for students wishing to spend more time in a specific specialty, conduct research and plan careers. Introduction to Surgery for Students is an edited collection of 31 chapters from a group of 80 medical students, junior doctors and consultant surgeons. Each chapter is written by a team made up of at least one student and one senior, and then edited and reviewed by a medical student with a special interest in the topic. This near-peer style of writing allows the content to cater to a student's needs at the right level, whilst having the expert input of surgeons who are leaders in their field. .
Keywords: Medicine.; Surgery.; Premedical education.; elektronické knihy; electronic books